1994
DOI: 10.4141/cjps94-071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wild mustard (Brassica kaber) competition on yield and quality of triazine-tolerant and triazine-susceptible canola (Brassica napus and Brassica rapa)

Abstract: . 1994. Effect of wild mustard (Brassica laber) competitioT 9l VigF g9 quality of triazine-tolerant and triazine-susdeptible canola (Brsssl'co nnpus anll Bmssica rapa). Can. J. Plant Research was conducted at two sites near Brandon, Manitoba, in 1990 and l99l to determine the influence of time of removal of wild mustard from triazine-tolerant (TT) or triazine-susceptible (TS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…Infestation of the weedy species in rapeseed fields causes heavy loss of the seed yield and reduction of the extracted oil and meal (Rose and Bell 1982;McMullan et al 1994). The requirements for more-economic and successful weed control in a rapeseed field and the advance of transformation technology have brought the transgenic B. napus to be tolerant to the herbicide glyphosate and glufosinate ammonium (Oelck et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Infestation of the weedy species in rapeseed fields causes heavy loss of the seed yield and reduction of the extracted oil and meal (Rose and Bell 1982;McMullan et al 1994). The requirements for more-economic and successful weed control in a rapeseed field and the advance of transformation technology have brought the transgenic B. napus to be tolerant to the herbicide glyphosate and glufosinate ammonium (Oelck et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Rapid leaf area production and greater initial height conferred on wild mustard the greatest competitive ability for light. S. arvensis densities of 10 plants m -2 can reduce canola seed yield by 20%, whereas 20 plants m -2 can reduce canola yield by more than 36% (Thomas 1984;Blackshaw et al 1987;McMullan et al 1994). McMullan et al (1994) found that wild mustard competition decreased harvested seed yield and quality of triazine-resistant and -susceptible canola (B. napus and B. rapa) in Manitoba.…”
Section: Economic Importancementioning
confidence: 99%
“…S. arvensis densities of 10 plants m -2 can reduce canola seed yield by 20%, whereas 20 plants m -2 can reduce canola yield by more than 36% (Thomas 1984;Blackshaw et al 1987;McMullan et al 1994). McMullan et al (1994) found that wild mustard competition decreased harvested seed yield and quality of triazine-resistant and -susceptible canola (B. napus and B. rapa) in Manitoba. Van Acker and Oree (1999) conducted crop interference studies of wild mustard and wild oat (Avena fatua L.) in canola (B. napus) in Manitoba.…”
Section: Economic Importancementioning
confidence: 99%
“…Weed contamination of oilseed rape crops may negatively impact the oil content of the crop by reducing oilseed rape yield through competition for resources (McMullan et al, 1994;Blackshaw et al, 2002;Beckie et al, 2008). A survey of oilseed rape crops in Australia found that weed incidence ranged from 49 weeds m À2 in triazine tolerant crops to 72 weeds m À2 in nontriazine tolerant cultivars (Lemerle et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in other countries on a limited number of weedy Brassicaceae species indicate the Brassicaceae weeds are high in antinutritional compounds both in the oil and meal (Hasapis et al, 1981;Horn & Vaughan, 1983). The Brassicaceae weed seeds may directly reduce oil content if they are not separated from the oilseed rape seed (McMullan et al, 1994). In addition, if oilseed rape seed lot admixtures with Brassicaceae weeds are not sufficiently cleaned prior to crushing, the resulting oil content and oil and meal quality could be reduced, particularly if the oil and meal characteristics of the weeds differ from the accepted oilseed rape quality standard.…”
Section: Introductionmentioning
confidence: 99%